In-room computed tomography–based brachytherapy for uterine cervical cancer: results of a 5-year retrospective study. (16th December 2016) - Ohno, Tatsuya; Noda, Shin-Ei; Okonogi, Noriyuki; Murata, Kazutoshi; Shibuya, Kei; Kiyohara, Hiroki; Tamaki, Tomoaki; Ando, Ken; Oike, Takahiro; Ohkubo, Yu; Wakatsuki, Masaru; Saitoh, Jun-Ichi; et al.
Abstract: Herein, we investigate the long-term clinical outcomes for cervical cancer patients treated with in-room computed tomography–based brachytherapy. Eighty patients with Stage IB1–IVA cervical cancer, who had undergone treatment with combined 3D high-dose rate brachytherapy and conformal radiotherapy between October 2008 and May 2011, were retrospectively analyzed. External beam radiotherapy (50 Gy) with central shielding after 20–40 Gy was performed for each patient. Cisplatin-based chemotherapy was administered concurrently to advanced-stage patients aged ≤75 years. Brachytherapy was delivered in four fractions of 6 Gy per week. In-room computed tomography imaging with applicator insertion was performed for treatment planning. Information from physical examinations at diagnosis, and brachytherapy and magnetic resonance imaging at diagnosis and just before the first brachytherapy session, were referred to for contouring of the high-risk clinical target volume. The median follow-up duration was 60 months. The 5-year local control, pelvic progression-free survival and overall survival rates were 94%, 90% and 86%, respectively. No significant differences in 5-year local control rates were observed between Stage I, Stage II and Stage III–IVA patients. Conversely, a significant difference in the 5-year overall survival rate was observed between Stage II and III–IVA patients (97% vs 72%; P  = 0.006). One patient developed Grade 3 late bladder toxicity. No other Grade 3 or higher late toxicities were reported in the rectum or bladder. In conclusion, excellent local control rates were achieved with minimal late toxicities in the rectum or bladder, irrespective of clinical stage.